Cardiac Glucose and Fatty Acid Transport After Experimental Mono- and Polytrauma. Issue 5 (May 2020) - Lackner, Ina; Weber, Birte; Knecht, Deborah; Horst, Klemens; Relja, Borna; Gebhard, Florian; Pape, Hans-Christoph; Huber-Lang, Markus; Hildebrand, Frank; Kalbitz, Miriam
ABSTRACT: Objective: The aim of this study was to define the influence of trauma on cardiac glucose and fatty acid transport. The effects were investigated in vivo in a porcine mono- and polytrauma model and in vitro in human cardiomyocytes, which were treated simultaneously with different inflammatory substances, mimicking posttraumatic inflammatory conditions. Methods and Results: In the porcine fracture- and polytrauma model, blood glucose concentrations were measured by blood gas analysis during an observation period of 72 h. The expression of cardiac glucose and fatty acid transporters in the left ventricle was determined by RT-qPCR and immunofluorescence. Cardiac and hepatic glycogen storage was examined. Furthermore, human cardiomyocytes were exposed to a defined trauma-cocktail and the expression levels of glucose- and fatty acid transporters were determined. Early after polytrauma, hyperglycemia was observed. After 48 and 72 h, pigs with fracture- and polytrauma developed hypoglycemia. The propofol demand significantly increased posttrauma. The hepatic glycogen concentration was reduced 72 h after trauma. Cardiac glucose and fatty acid transporters changed in both trauma models in vivo as well as in vitro in human cardiomyocytes in presence of proinflammatory mediators. Conclusions: Monotrauma as well as polytrauma changed the cardiac energy transport by altering the expression of glucose and fatty acid transporters. In vitro data suggest that human cardiomyocytes shift to a state alike myocardial hibernation preferring glucose as primary energy source to maintain cardiac function. Abstract : Supplemental Digital Content is available in the text